Awareness, Safety Practices and Associated Factors Among E-Waste Recycling Workers in Bangladesh - Meherun Nahar Munni; Mohammad Rezaul Karim; Mohibbul Haque; Sumaiya Khan; Md Abdullah Saeed Khan; Irin Hossain (SAGE Publishing, 2024)
Awareness of electronic waste (e-waste) improves safety practices among workers, thereby reducing health risks associated with pollutants. Investigating the awareness and safe practices among these workers could help identify areas for improvement, a task not yet undertaken in Bangladesh. Consequently, this study aimed to examine the awareness, safety measures, and associated factors among e-waste workers in the country. In this cross-sectional study, 236 workers from an e-waste recycling facility located near Dhaka were interviewed using a semi-structured questionnaire from August to September 2022. Eight questions captured information on socio-demographics and work factors, 24 questions on e-waste awareness, and 11 questions on safety practices. Total awareness and safety scores were calculated and categorized as "good" and "poor" based on a cut-off point of 80% of the total score. Bivariate and regression analyses were done to determine associated factors. Only 25% of workers had good e-waste awareness; major knowledge gaps were regarding minimization, health hazards, and environmental impact. Good awareness was significantly associated with female gender, higher education, income, smoking, experience ⩾5 years, and training. About 58% followed good safety practices, but the use of boots and helmets was inadequate. Good safety practices were significantly associated with higher education, income, smoking, experience, training, and overtime work. On multivariable analysis, those with higher education had 12 times (95% CI 4.83-32.81) and 6 times (95% CI 2.94-12.81) higher odds of good awareness and practices, respectively. Trained workers had 3.6 times (95% CI 1.67-7.52) higher odds of good practices. There was a significant correlation between awareness and practices (r = .70, P < .001). The study found poor awareness and inadequate safety practices related to e-waste among the workers. Urgent interventions like training, the use of protective gear, and stringent policies are warranted to increase awareness and safety behaviors.